Ortodoks teologi ved en skillevej - Emil Hilton Saggau (Svensk Teologisk Kvartalskrift)
When Russian troops entered Ukrainian territory in February 2022, it opened up a new bloody chapter in European history. The military confrontation is deeply entangled with a religious shaped image arisen from the Russian Orthodox Church and the long history of state–church relations in the Orthodox world. This relationship to the state is a pragmatic embrace of secular power with theological roots, but the war has revealed the tension in Orthodox political theology. The state-embracing ideal is in contrast to the monastic ideal of a heavenly citizenship, which refuses to be deployed by the state. The political alliance between state and church has theological implications that continue to be present in the war preaching of the Russian Patriarch Kirill through 2022. In opposition stands an emerging new theological position in Ukraine, the Maidan theology, of among others Cyril Hovorun. This paper is an assessment of these two positions and their complex relationship in Orthodox theology in light of the war. The analysis points towards traditions of both of these two ideals in the early church; traditions that have become a point of reference in Orthodox political theological debates.